A review on diseases manifestation by ocular diseases using computer aided diagnosis (CAD) - Ramlee, Ridza Azri; Ramli, Abdul Rahman; Sulaiman, Hamzah Asyrani (Engg Journals Publications, 2015)
The use of eye for diagnosis for detecting the disease has been used long time ago. However, for conventional medical practitioners this procedure are used to detect diseases that cause vision problems. This method is widely used by practitioners of alternative medicine that uses the eyes to detect the presence of disease, such as iridology practitioners. In this paper we study the method adopted by the researchers based on conventional and alternative medical practitioners to detect the presence of disease using a computer-aided diagnosis (CAD) or automatically.